Kesepahaman Nilai Pancasila Dengan Nilai Kristiani Berdasarkan Injil Matius 22:39-40 - Rambu Boba, Ervin; Adi Saingo, Yakobus (CV. Multi Kreasi Media, 2023)
Pancasila is the basic ideology of the Indonesian state which is the standard of behavior for its people. The ideological values ​​of Pancasila are in agreement with Christian teachings because they both encourage every community to live a correct spiritual life, and must also be balanced with a harmonious social life with others. The aim of this research is to discuss the agreement between Pancasila values ​​and Christian values ​​based on the teachings in Matthew 22:39-40. The method used in this research article is literature study by conducting a review of various scientific literature, such as proceedings, reference books, scientific journals to be developed in a series of narratives. Data analysis was carried out descriptively which explained the results that Christian teaching, especially those based on the book of Matthew 22:39-40, has an understanding or harmony with the values ​​of Pancasila which can be measured by truly becoming a society that loves God according to its beliefs and manifests love for each other by avoiding various forms of discriminatory attitudes that can cause divisions between fellow members of the nation. Pancasila and Christian values ​​both contain values ​​such as mutual cooperation, social justice and unity, which, if deeply internalized by society, can become the basis for creating harmony and unity.